Micro-friction mechanism characterization of particle-reinforced multilayer systems of 316L and 430L alloys on grey cast iron - Mohammad Masafi; Heinz Palkowski; Hadi Mozaffari-Jovein (Journal of Materials Research and Technology)
Grey cast iron with lamellar graphite (GJL) is renowned for its exemplary damping properties and elevated thermal conductivity, which are attributable to its distinctive lamellar graphite structure. The present study investigates the potential of laser metal deposition (LMD) as a coating process to enhance the corrosion resistance and wear mechanisms of this tribological system. Given the critical safety-related function of GJL brake discs, it is of paramount importance to avoid manufacturing defects in the coatings applied to them. This paper addresses the subject of laser cladding on GJL utilizing the stainless steel materials 430L and 316L in conjunction with TiC and WC particles. A multi-layer cladding system was employed to fabricate the samples. Prior to and following the application of a brake shock corrosion test, which simulated the conditions prevalent in the automotive industry, an investigation was conducted into the surface properties and microstructure of the interfaces, as well as the behavior of the graphite lamellar during laser cladding.The results demonstrated that a subset of samples exhibited severe delamination and cracking following the test. Specifically, the sample comprising 316L as both the first and second coating layers and WC particles (Sample 3) exhibited pronounced cracking and delamination, whereas the sample with 316L as the first layer and 430L with TiC particles as the second layer (Sample 6) demonstrated superior performance. Furthermore, a dilatometric test was performed to elucidate the interaction between the thermal expansions of the coatings and the substrate. The temperature increase that occurs during the braking process affects various components of the braking system, including wear and thermal expansion. For example, the discrepancy in thermal expansion between 316L and GJL at 500 °C was determined to be 0.03 mm in length and 0.14 mm2 in area. The presence of WC in the coating resulted in a downward slope in the expansion coefficient during the phase transition to austenitization, whereas TiC exhibited an upward slope.It is of paramount importance to gain an understanding of the thermal effects on a range of materials, including coatings and substrates, in order to optimize brake performance and ensure safety. Furthermore, the study underscored the significance of preheating the substrate to mitigate residual stresses and avert hot cracking, thus enhancing the adhesion and durability of the coating.